Effect of intraoperative blood transfusion on inflammatory response in parturients with placenta previa undergoing cesarean section: A prospective observational study. Issue 2 (February 2023) - Sim, Ji-Hoon; Cho, Hyun-Seok; Jang, Dong-Min; Park, Hee-Sun; Choi, Woo-Jong; Park, Jong Yeon
Abstract: Background: The neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and red cell distribution width (RDW) have been reported as useful biomarkers for evaluating inflammation and a predictor of surgical prognosis. Although there have been recent reports that transfusion may affect inflammatory responses, studies on the post-transfusion inflammatory response in parturients are rare. Therefore, this study aimed to observe changes in inflammatory response after transfusion during cesarean section (C-sec) through NLR, PLR, and RDW. Methods: Parturients aged 20–50 years who underwent C-sec under general anesthesia due to placenta previa totalis from March 4, 2021, to June 10, 2021 were participated in this prospective observational study. We compared postoperative NLR, PLR, and RDW between the transfusion and non-transfusion groups. Results: A total of 53 parturients were included in this study, of which 31 parturients received intraoperative transfusions during C-sec. There were no significant difference in preoperative NLR (3.6 vs. 3.4, p = 0.780), PLR (132.8 vs. 111.3, p = 0.108), and RDW (14.2 vs. 13.6, p = 0.062) between the two groups. However, postoperative NLR was significantly higher in the transfusion group than in the non-transfusion group (12.2 vs. 6.8, p < 0.001). Postoperative RDW was significantly higher in the transfusion group than in the non-transfusion group (14.6 vs. 13.9, p = 0.002) whereas postoperative PLR was not significantly different between the two groups (108.0 vs. 117.4, p = 0.885). Conclusions: Postoperative NLR and RDW, the inflammatory biomarkers, were significantly higher in the transfused C-sec parturients. These results suggest a significant association between postoperative inflammatory response and transfusion in obstetric practice.